Peran Program Kerja Sanggar Seni Sedulang Setudung Terhadap Perkembangan Tari di Kecamatan Banyuasin III - Sahputri, Nopi; Elvandari, Efita; Hidayatullah, Fadhilah (Indonesian Research Journal on Education, 2023)
The objectives to be achieved from this research are to know the concept of the work program of the Sedulang Setudung art studio and to know and describe the role of any work programs that affect the Sedulang Setudung art studio to the development of the Sedulang Setudung dance in Banyuasin III district. The focus of this research is the work program of the Sedulang art studio. The method used in this research is to use qualitative methods. Data collection techniques in this study are by observation, interviews and documentation. The results of his research from the dance performances and competitions that were followed were an effort to spread the dance to be more widespread and known to the public through the Sedulang Setudung art studio that exists to this day and has received various awards, trophies, charters. and began to be in great demand by young people in the Banyuasin III sub-district with the existence of the Sedulang Setudung art studio, making it a place to get to know the traditional dances of the Banyuasin district, especially the Sedulang Setudung dance which is a mandatory dance in the Banyuasin district in order to remain sustainable.